Association between aspartate aminotransferase to alanine aminotransferase ratio and 28-day mortality of ICU patients: A retrospective cohort study from MIMIC-IV database - Yanping Wang; Yan Xu (PLoS ONE, 2025)
Background Prior studies have linked the aspartate aminotransferase to alanine aminotransferase ratio (AAR) with negative health outcomes in the elderly and specific populations. However, the impact of AAR on the prognosis of the entire population in the intensive care unit (ICU) remains unclear. This study aimed to determine the correlation between AAR and the mortality among adult ICU patients. Method Patient data were retrieved from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database and stratified into quartiles by AAR. Survival analysis using the Kaplan-Meier curves was conducted to compare survival across quartiles. The primary outcome was 28-day mortality, with secondary outcomes including 60-day, 90-day, and 365-day mortality, along with ICU-free, ventilator-free, and vasopressor-free days within the first 28 days. The association between AAR and mortality was evaluated using Cox proportional hazards regression analysis complemented by a restricted cubic spline. Furthermore, the eICU Collaborative Research Database (eICU-CRD) was used as an external validation cohort for sensitivity analysis. Result The study included 20,225 patients with a mean age of 63.7 ± 17.5 years. Kaplan-Meier analysis indicated a higher risk of 28-day mortality for patients with higher AAR (log-rank P < 0.001). After adjusting for confounders, the AAR was significantly related to 28-day mortality (HR = 1.04, 95% CI: 1.03–1.06, P < 0.001) and other mortality benchmarks, exhibiting an inverted L-shaped relationship. The inflection point of the AAR for 28-day mortality was 2.60. Below this threshold, each unit increase in the AAR was associated with a 19% rise in the risk of 28-day mortality (HR = 1.19, 95% CI: 1.11–1.27, P < 0.001), with a plateau observed above this threshold. Subgroup and sensitivity analyses further confirmed the robustness and generalizability of the study. Conclusion AAR demonstrated a significant association with 28-day, 60-day, 90-day, and 365-day mortality, characterized by an inverted L-shaped pattern.